SELECTIVE IMMIGRATION POLICY IN MAINTAINING STATE SECURITY AND IMPROVING THE WELFARE OF THE NATION - Firman Gunawan; Kevin Pramudya; M. Ridwan Ari Hermawan (Universitas Labuhanbatu, 2023)
This writing aims to look at the role of selective immigration policies in Indonesia in order to maintain state security and improve the nation's welfare. The implementation of selective policy in Indonesia is the most important thing that cannot be ignored, the principle of selective policy looks at security and welfare approaches. Two of the functions of immigration are state security and facilitator of community welfare development. Currently, indicators of state security and the economy of a nation have become important aspects of the state. Considering that currently the movement of people between countries is becoming easier and global economic development is becoming more widespread, there will be an impact on these two factors. Selective immigration policy is a form of legal product from immigration related to regulating the entry of foreigners into Indonesia with an approach to the principle of benefits for the nation and state. This research method uses normative legal research methods with a descriptive qualitative approach.Keywords: Selective Policy, State Security, WelfareÂ